The analysis of photonic crystal fibers opticalgeometrical properties and their impact on transfer parameters - Filipenko, A.; Donskov, A.; Sychova, O. (Технологический центр, 2012)
In microstructured optical fibers some defects are inherent to the fabrication process. One can mention, for example, the inhomogeneity of the initial preform: diameter, position of the inclusions (when the hexagonal stack is assembled before drawing) and refractive index that evolves along its axis. These defects will lead to transverse disorders in the final fiber. Therefore, the analysis of photonic crystal fibers optical-geometric properties and their impact on transfer parameters is very important. We note that in our investigation we use finite-element method. The obtained results show that at any of considered defect types the mode field will have two pronounced maximums. The results presented in this work show that total mode field power increases with decreasing the mean diameter of air holes. Another important result is that random variations of diameter of inclusions (air holes) can lead to an increase of total mode field power. We also have shown that random variations of inclusions diameter can increase the total mode field power. In the part 2 the signal losses caused by the difference of mode fields effective areas of connected fibers are determined. Further research in this sphere is directed to the study of influence of other optical-geometric PCF parameters, as well as their connection to the signal transmission. All presented results will be helpful for tolerance of fabrication processes and for better understanding the role of random variation of geometrical behaviors (arising at fabrication processes) on operation parameters of microstructured optical fibers.
Keywords: photonic crystal fiber; quartz; photonic-bandgap; index contrast; Gaussian distribution